Role of LONELY GUY genes in indeterminate nodulation on Medicago truncatula - Mortier, Virginie; Wasson, Anton; Jaworek, Pavel; De Keyser, Annick; Decroos, Martijn; Holsters, Marcelle; Tarkowski, Petr; Mathesius, Ulrike; Goormachtig, Sofie (The New phytologist, 2014)
LONELY GUY (LOG) genes encode cytokinin riboside 5'-monophosphate phosphoribohydrolases and are directly involved in the activation of cytokinins. To assess whether LOG proteins affect the influence of cytokinin on nodulation, we studied two LOG genes of Medicago truncatula. Expression analysis showed that MtLOG1 and MtLOG2 were upregulated during nodulation in a CRE1-dependent manner. Expression was mainly localized in the dividing cells of the nodule primordium. In addition, RNA interference revealed that MtLOG1 is involved in nodule development and that the gene plays a negative role in lateral root development. Ectopic expression of MtLOG1 resulted in a change in cytokinin homeostasis, triggered cytokinin-inducible genes and produced roots with enlarged vascular tissues and shortened primary roots. In addition, those 35S:LOG1 roots also displayed fewer nodules than the wild-type. This inhibition in nodule formation was local, independent of the SUPER NUMERIC NODULES gene, but coincided with an upregulation of the MtCLE13 gene, encoding a CLAVATA3/EMBRYO SURROUNDING REGION peptide. In conclusion, we demonstrate that in M. truncatula LOG proteins might be implicated in nodule primordium development and lateral root formation.
Keywords: proteiny huseníčku; root growth; aminohydrolasy; tvorba kořenových hlízek; Genes, Plant; Up-Regulation; kořenové hlízky rostlin; Plant Roots; proteinkinasy; Arabidopsis Proteins; upregulace; jaderné proteiny; nodulation; Root Nodules, Plant; receptory buněčného povrchu; Plant Proteins; Aminohydrolases; Cytokinins; regulace genové exprese u rostlin; kořeny rostlin; Plant Root Nodulation; cytokininy; nodule primordium; Medicago truncatula; Protein Kinases; cytokinin; Gene Expression Regulation, Plant; Receptors, Cell Surface; rostlinné geny; LONELY GUY; Nuclear Proteins; rostlinné proteiny